Resistance training variables on muscle hypertrophy: a systematic review - Machado,Wanderson Matheus Lopes (2022)
ABSTRACT Resistance training (RT) is a widely practised type of training, and the number of adherents of this type of physical exercise is increasing each year. Among the most sought objectives of those who initiate RT is muscle hypertrophy, although success in this process depends on a well-designed protocol and good manipulation of training variables. The present study aims to analyse, through a systematic review, the impact of the RT variables (such as intensity, volume, recovery interval, execution speed, and concentric muscle failure) relevant to muscle hypertrophy and if there is an ideal range for each training variable. The research was carried out in the PubMed, Web of Science, Scopus and Scielo databases from 2000 to 2020, using the terms “resistance training” and “hypertrophy” and “intensity” or “volume” or “recovery interval” or “execution speed” or “muscular failure”. Twenty-three articles were included in the review. The PEDro scale was used to analyse the quality of the selected articles. It was concluded that the variables intensity and volume must be carefully analysed in a training program. Despite not having a direct impact on hypertrophy, the other variables affect the intensity and volume and must be manipulated according to what is intended with the others.